Improving E-government services for advanced search - Šimić, Goran P. (Vojnotehnički glasnik / Military Technical Courier, 2019)
The E-government services depend on many archived documents mostly scanned and partially described to be machine searchable in order to be found fast and to offer appropriate responses to citizens and to the government personnel as well. In order to improve the existing state, the hybrid solution based on the previous research results is presented. This paper presents an in-depth view of the Web solution that combines different technologies on both the client and the server side thus improving regular search services amd making them accessible to people with dissabilities (e.g. blindness).